PENGEMBANGAN E-LKPD DENGAN MODEL INKUIRI TERBIMBING BERBASIS ANDROID PADA MATERI KINGDOM PLANTAE UNTUK PESERTA DIDIK SMA KELAS X - Evi Agustina; Muhfahroyin Muhfahroyin; Agus Sujarwanta (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The aims of developing LKPD with an Android-based guided inquiry model can provide innovations in the learning process by utilizing increasingly sophisticated information technology. To minimize problems that occur in the learning process during the pandemic. The development method uses the Thiagarajan, 4-D model, this model consists of 4 stages of development, namely define, design, develop, and disseminate. The results of product development The e-LKPD product that has been developed is valid and feasible to use and can be used as an alternative to solving problems in the learning process found at SMA IT Cinta Illahi, by using the e-LKPD it is hoped that the learning process will be more efficient, the direction of learning is participant-centered so that students can find and solve problems by the direction of the teacherKata Kunci :e- LKPD, Inkuiri Terbimbing, Plantae